Molecular ingredients of an immunogen for long-lasting IgG - Gupta, Sneh Lata; Meyer, Alexander R.; Kay-Tsumagari, Erika; Cheng, Wei (Frontiers in Immunology, 2025)
The durability of vaccine-induced protection is a critical parameter in assessing the overall quality and long-term effectiveness of a vaccine. While the lifelong immunity conferred by certain vaccines is well recognized, the molecular components that underpin such long-lasting protection remain poorly understood. This knowledge gap is further complicated by the frequent inclusion of adjuvant formulations in licensed vaccines, the mechanisms of which are often multifaceted and not fully elucidated. In this review, drawing upon the portfolio of FDA-approved antiviral vaccines and incorporating insights from our own published studies in rodents, we propose that a virus-like structure - devoid of any engineered adjuvants - is all that is needed for a long-lasting IgG response in both mice and humans. This structure comprises two essential features: (1) the oriented display of viral surface protein antigens on a virus-sized scaffold, and (2) internal nucleic acids with native phosphodiester backbones. In fact, several inactivated virus vaccines that conform to this architecture have demonstrated effective and durable protection in human populations without the need for engineered adjuvants. Clarifying these structural and molecular determinants of viral immunogenicity may reduce the empirical nature of vaccine development, enable the rational design of next-generation self-adjuvanting antiviral vaccines, and inspire novel applications in noncommunicable diseases.